A comprehensive review of acoustic based leak localization method in pressurized pipelines. (December 2021) - Hu, Zhongyu; Tariq, Salman; Zayed, Tarek
Highlights: This paper only focuses on the acoustic-based leak localization methods in a pipeline system. Scientometric analyses are quantitatively conducted. Cross-correlation is found to be the most frequently employed theory basis. Research limitations and gaps, as well as suggestions for future directions, are summarized. Abstract: Pipelines are widely used in the transportation of water, oil, gas, etc. Leakage in pipelines leads to a great waste of natural resources and sometimes constitutes a public health risk. Due to its wave-like nature, acoustics is one of the most studied technology for leak detection and localization in pipelines. Over the past decades, numerous articles have been published to address leak localization problems with acoustic-based methods. However, a review of the research development on acoustic-based leak localization technology is lacking. Therefore, this paper utilizes bibliometric analysis to systematically examine the published research articles in this field. Analyses showe that investigations on acoustic-based leak localization technology became popular in the last decade. Most existing researches focus on or exploited the cross-correlation based methods. Furthermore, the most frequently investigated research objective is the development of a signal processing algorithm for denoising and extracting leak signals. Other efforts include altering the number of sensors, developing wireless detection systems, etc. Potential future directions are presented based on a summary of the limitations of the existing research. This paper provides an in-depth understanding of the state-of-the-art in this field to researchers and engineers. Additionally, it identifies prospective research areas based on the findings and limitations of the previous studies.